Konsep Hak Milik Dalam Ekonomi Islam - Ade Vitria; Annisa Syafriani (AGHNIYA : Jurnal Ekonomi Islam, 2023)
Ownership is a significant problem in human life, because it is an essential component of existence. Without means, people cannot satisfy all their physical or instinctive needs, and therefore they strive to obtain what is absolutely necessary. The capitalist system which prioritizes the regulation of individual property rights, and the socialist system which does not recognize individual property rights are very different from the Islamic understanding of ownership. Islam accepts both private and state property, and even considers private property rights to be the foundation of economic growth. This study used qualitative research methods. This qualitative research method usually uses secondary data in the form of data that has been published in any form as a reference, such as e-books, printed books, scientific journals, and other scientific works. According to Islamic beliefs, Allah is the only One who bestows upon mankind unlimited blessings and sustenance. Therefore, all wealth and property belongs to God, humans (people) only have it temporarily because of a trust or gift from God. Humans do not use assets as permanent owners, but as trustees. Since Allah is the owner of everything in this world, it seems reasonable that He should have total power, making all provisions as guidelines as long as they are found in the Qur'an.